Journal of Human Genetics - Matsumoto, Naomichi; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer Nature.)
The Journal of Human Genetics is an international journal publishing articles on human genetics, including medical genetics and human genome analysis. It covers all aspects of human genetics, including molecular genetics, clinical genetics, behavioral genetics, immunogenetics, pharmacogenomics, population genetics, functional genomics, epigenetics, genetic counseling and gene therapy. Articles on the following areas are especially welcome: genetic factors of monogenic and complex disorders, genome-wide association studies, genetic epidemiology, cancer genetics, personal genomics, genotype-phenotype relationships and genome diversity. - Medical genetics - Human genome analysis - Gene cloning and mapping - Linkage and association analyses - Rare variants in diseases and phenotypes - Mutational analysis - Susceptibility genes to multifactorial disorders - Human evolution - Cancer genetics - Gene therapy - Genetic and functional analysis of animal models of disease or behaviour - Genetic polymorphisms of biologically important genes - Novel mutations found in patients with hereditary diseases - Novel mutations found in cancer cells - Population genetics - Human diseases with epigenetic or chromatin dysregulation - Human epigenome analysis - Noncoding RNAs - Developmental Origins of Health and Disease - Prenatal diagnosis - Molecular cytogenetics and genomic structural variation.
Keywords: Human genetics; Gene expression; Gene therapy; Medical genetics; Molecular biology; Human Genetics; Molecular Medicine; Gene Function; Gene Expression; Gene Therapy